Determinants of cash holdings of firms listed on the Ghana stock exchange - MAWUNYO ADZO TIMPO OLIVIA (KNUST, 2024)
A thesis submitted to the department of accounting and finance Kwame Nkrumah university of science and technology school of business in partial fulfillment of the requirements for the degree of executive master of business administration (finance) school of business, college of humanities and social sciences Kwame Nkrumah university of science and technology